Exploring the feasibility of the asthma self- management booklet to empower adults with asthma among family medicine physicians - Nik Mohd Nasir, Nik Munirah; Abdul Razak, Suraya; Ramli, Anis Safura; Abd Halim, Haizlene; Abdul- Hamid, Hasidah (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
The development of a user-centered healthcare intervention tool would require feasibility testing to evaluate the acceptability, usability, strengths, and weaknesses of the tool. Feasibility testing evaluates the intervention's potential for success; therefore, exploring the user’s experience, acceptability, opinion, and motivation is an important factor in the evaluation process [1]. To ensure that the Asthma Self-Management Booklet© is acceptable and useful to physicians in managing adults with asthma, there is a need to systematically evaluate the feasibility of these tools in supporting and empowering self-management of their patient’s asthma symptoms [2]. Therefore, the objectives of this project are to explore the feasibility of the Asthma Self-Management Booklet© in empowering patients in asthma self-management and to refine the booklet based on the feasibility assessment findings. A qualitative research design using focus group methodology will be employed to explore the acceptability, usability, strengths, and weaknesses of the Asthma Self-Management Booklet©.